Analisis Clinical Pathway Dengan BPJS Antara RS Negeri Dan RS Swasta - Wijayanti, Fitria Eka Resti, Prof. Dr. dr. Rusdi Lamsudin Sp.S (K), Drs. M. Farid Wajdi, MM., Ph.D (2016)
This study aimed to analyze the application, preparation and supervision of implementation of clinical pathways with BPJS between public hospital and private hospitals. The type of this study is qualitative research. Informants in this study are Director, Chairman of the Medical Committee, Head Nurse room and Chief Pharmacy. Methods of data collection using interviews, observation and documentation. Data analysis techniques using interactive model analysis. The results showed that the clinical pathway has been applied in the Dr Moewardi Hospital and PKU Muhammadiyah of Surakarta Hospital based on Regulation Health Minister No. 012 of 2012 About the Hospital Accreditation. Preparation of clinical pathways preparation technically is to determine the problem, pointing coordinator, determine the parties involved, prepare literature, identifying the needs of the patient, make CPG adjustments (Clinical Practice Guidelines), reducing activity and costs and anticipated errors (Freud), and the last is set of processes and outcomes. Supervision of the clinical pathways implementation conducted by those responsible for the hospital with regular and sustainable evaluation. Problems were found from the results of supervision of the clinical pathways implementation are 1) the doctors responsible for the patient's adherence to clinical pathways is still lacking, 2) lack of concentration in charging clinical pathway development, 3) difficulty certainty of the use of clinical pathways, when to drop and when to use because of clinical pathways should be without complications.